Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fmicb.2021.739572
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplementing Intestinal Autochthonous Bacteria in Plant-Based Diets on Growth, Nutrient Digestibility, and Gut Health of Bullfrogs (Lithobates catesbeianus)

Abstract: Poor utilization efficiency of plant protein diets always leads to intestinal barrier dysfunction and growth inhibition in animals. Probiotics have shown promise in improving growth performance and gut health of the host. However, obtaining the host-beneficial probiotic from thousands of bacterial phylotypes is challenging. Here, four intestinal autochthonous bacteria were isolated from fast-growing bullfrog after a 60-day feeding on a soybean meal (SM)-based diet. Another feeding trial was conducted to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Intestinal microbiota play an important role in the health, immunity, metabolism, development, and reproduction of fish [73]. Dietary nutrition is a critical factor in determining the makeup of the trillions of bacteria that reside in the intestine [74]. Labaw et al [75] demonstrated that P, as a component of nucleic acid and other biochemical molecules, played a vital role in microorganism growth [76].…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal microbiota play an important role in the health, immunity, metabolism, development, and reproduction of fish [73]. Dietary nutrition is a critical factor in determining the makeup of the trillions of bacteria that reside in the intestine [74]. Labaw et al [75] demonstrated that P, as a component of nucleic acid and other biochemical molecules, played a vital role in microorganism growth [76].…”
Section: Discussionmentioning
confidence: 99%
“…The commercially available kits (Nanjing Jiancheng Bioengineering Institute, Nanjing, China; A045-4-2, A054-2-1, C016-1-1, A080-2-2, and A080-1-1) were used to determine the total protein content and the activities of lipase, amylase, trypsin, and pepsin in tissues. The total protein content, lipase and amylase activity, and trypsin and pepsin activity were determined as described by Wang et al (2021b), Lu et al (2020), and Zhang et al (2020b), respectively. The determination process was strictly based on the instructions, and absorbance values of total protein content, lipase, amylase, trypsin, and pepsin were measured at 562, 580, 660, 253, and 660 nm, respectively, using a microplate reader (Synergy2; BioTek Inc., USA) and a UV spectrophotometer (UV-5100; Shanghai Metash Instruments Co., Ltd, Shanghai, China).…”
Section: Digestive Enzyme Activity Analysesmentioning
confidence: 99%